THE EFFECT OF MUNDU FRUIT (Garcinia dulcis (ROXB.) KURZ) METHANOL EXTRACT ON LYPHOPROTEIN PROFILE AND TRYGLISERIDE WHITE RAT (Rattus norvegicus L) - Arum Setiawan; Laila Hanum; Elvi Rusmiyanto Pancaning Wardoyo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Garcinia dulcis (Roxb.) Kurz) (Guttiferae) is a tropical fruit tree native to Indonesia and its known as an Asian medicinal plant used in folk medicines. In ethno pharmacology, Garcinia dulcis has been used in traditional medicine, such as anti-inflammatory, anti-tumor, anti-malaria and anti-bacterial. The scientific studies of biological activity of Garcinia dulcis on lipide profile and trigliseride are relatively measly. Therefore, the objectives of this research were to know the effect of methanol extract of Garcinia dulcis fruit on total cholestrol, low density lipoprotein-cholesterol, high density lipoprotein-cholesterol and triglyseride rat hyperlipidemic. These studies using Garcinia dulcis fruit from Banyuasin, South Sumatra. In this observation, 30 male rat from Laboratory and Research Institute for Integrated Testing, Gadjah Mada University, 2 months old were used and divided into five groups randomly. The first group was given high cholesterol and lipid diet, as a normal group. The second group was given high cholesterol, lipid diet and simvastatin 3,6 mg/kg bow/day dosage, as a simvastatin group. The third, fourth and fifth groups was given high cholesterol, lipid diet and methanol extract 1.8; 2.7 and 3.6 mg/kg bow/day dosage. Total cholestrol, low density lipoprotein-cholesterol, high density lipoprotein-cholesterol and triglyseride contains using spectrophotometry method, were observed 1 and 30 days. The differences among groups were analyzed using Anova followed by LSD to locate the differences. LSD analysis showed that Garcinia dulcis methanol extract treatment doses of 3.6 mg/kg bw and simvastatin lowers total cholesterol levels highest in the amount of 32.17 mg/dL and 24.1 mg/dL, significantly different compared with the treatment dose of 1.8 mg/kg bw. Garcinia dulcis fruit methanol extract treatment doses of 3.6 mg/kg bw and simvastatin lowers triglyceride levels by 7.22 mg/dL and 24.58 mg/dL, significantly different compared with the treatment dose of 1.8 mg/kg bw and controls. Garcinia dulcis fruit extract dose of 3.6 mg/dL lower low density lipoprotein-cholesterol highest of 16.45 mg/dL. Garcinia dulcis fruit methanol extract dose of 3.6 mg/kg bw was also able to increase the levels of high density lipoprotein-cholesterol by 5.62 mg/dL. The results showed that the fruit of Garcinia dulcis contain compounds that have potential as agents antihiperlipidemia and presumably through inhibition of the enzyme HMG-CoA reductase.